Information fusion model-free adaptive control algorithm and unmanned surface vehicle heading control. (September 2019) - Jiang, Quanquan; Li, Ye; Liao, Yulei; Miao, Yugang; Jiang, Wen; Wu, Haowei
Abstract: Based on the model-free adaptive control (MFAC) theory, the heading control problem of unmanned surface vehicles (USVs) with uncertainties is explored. First, as a USV's heading subsystem does not satisfy the quasilinear assumption of the MFAC theory, a new type of input and output information fusion MFAC, i.e., the IOIF–MFAC algorithm is proposed. The novel algorithm proposed herein renders the MFAC theory applicable to the heading control of USVs. Next, the input and output information of the heading subsystem, namely the rudder angle and heading angle, are combined, and the data model of the heading subsystem is subsequently deduced using a compact format dynamic linearization method. Based on which, the stability of the control system is proved. Finally, the effectiveness and practicability of the IOIF–MFAC algorithm are verified by simulation and field experiments through the "Dolphin IB" test platform developed by our group.